Corrigendum to “The apolipoprotein gene: a modulating role on brain volume and cognitive function in carriers of the fragile X premutation” [Neurobiology of Disease 2026 Feb 2; 220:107292, Page 1–13] - Jiraanont, Poonnada; Wang, Jun Yi; Durbin-Johnson, Blythe; Hwang, Ye Hyun; Hessl, David; Rivera, Susan M.; Hagerman, Randi J.; Tassone, Flora (My University, 2026)
The authors regret that they omitted to submit updated captions for Figs. 1, 2 and 3 during revision. The correct figure captions are as follows. Fig. 1 Representative segmentations of white matter hyperintensities (A-F), whole brain (G-L), cerebellum (G-L), brainstem (G-L), and lateral ventricles (LV, G-L) in a healthy control (A, D, G, & J), a premutation carrier without FXTAS (B, E, H, & K), and a premutation carrier with FXTAS (C, F, I, & L) all at the age of 62 years. (A-C) Axial views of the FLAIR scans showing segmented white matter hyperintensities including the splenium sign of the corpus callosum (dash arrow) in C. (DF) Coronal views of the FLAIR scans showing the segmented white matter hyperintensities including the splenium sign of the corpus callosum (dash arrow) and the MCP sign (straight arrows) in F. (G-I) Sagittal views of the T1 images showing the segmentation of the brain, cerebellum, brainstem, and LV. (J-L) Coronal views of the T1 images showing the segmentation of the brain, cerebellum, brainstem, and LV.